Correlation of Calcium Levels With The Strenght of Uterus Contraction on The Active Phase of First Stage Labor - Novia Rita Aninora; Joserizal Seridji; Meilinda Agus (Universitas Andalas, 2018)
Contributing factor to uterus contraction mechanism is the imbalance of the extracellular calcium level. When extracellular calcium level is inadequate, response of the myometrium to oxytocin decreased and the calcium influx inter-cell membranes are suppressed, thus inhibit uterine contractions. The aim of this research is to know the correlation between levels of calcium and the strength of uterine contraction in the active phase of first stage labor. This was a cross-sectional analytic correlative study in the Dr. Rasidin Hospital Padang and UPTD Health Laboratory in West Sumatra province, in was conducted from November 1st, 2014 till February 2016. Sampling was takes by using non probability sampling with consecutive sampling. Subjects of this research were the active phase of first stage labor of 62 people. Kolmogorof Smirnov normality test was used to the normality of the data. Pearson correlation test was conducted to examine the correlation between dependent and independent variables. Mean levels of calcium in the the stage I of labor respondents active phase (8.94 ±0,71), while mean strength of uterine contractions in active phase of first stage labor(56.77±11,84), there was positive correlation (r = 0,62) between the levels of calcium in the strength of uterine contractions (p < 0.05). The conclusion of the study there was a significant correlation between the levels of calcium in the strength of uterine contractions.